2010
DOI: 10.3176/eco.2010.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication level ofPhragmites australishabitats at a shallow coastal lake, Paljassaare Peninsula, Tallinn, Estonia

Abstract: The eutrophication level of a lake situated in the centre of the Paljassaare Peninsula, Estonia, was estimated using chemical characteristics of common reed (Phragmites australis). Comparison with other Estonian waterbodies revealed considerable differences. The N and P concentrations in the leaves and the N concentration in the stems of P. australis during the phenophase of early flowering were in Paljassaare (data from 11 sampling sites) 1.5-2-fold higher than in the eutrophic Lake Võrtsjärv, in the high-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…High nutrient content in the tissues of European native and Far Eastern populations agree with their high invasive potential indicated by their vigorous growth, and also with the invasion success of European clones in North America (Meyerson et al 2009). The leaf-nitrogen values in our experiment were close to the maxima found in plants cultivated under high supply of nutrients (Clevering 1998) and to the maxima found in the field (Kohl et al 1998, Farnsworth & Meyerson 2003, Baldantoni et al 2004, Soetaert et al 2004, Elvisto 2010. The pattern of the highest leaf-nitrogen values in European clones followed by North American invasive and North American native genotypes (Guo et al 2014) was confirmed in our experiment.…”
Section: Nitrogen Phosphorus and Carbon In Leaves Rhizomes And Rootssupporting
confidence: 88%
See 1 more Smart Citation
“…High nutrient content in the tissues of European native and Far Eastern populations agree with their high invasive potential indicated by their vigorous growth, and also with the invasion success of European clones in North America (Meyerson et al 2009). The leaf-nitrogen values in our experiment were close to the maxima found in plants cultivated under high supply of nutrients (Clevering 1998) and to the maxima found in the field (Kohl et al 1998, Farnsworth & Meyerson 2003, Baldantoni et al 2004, Soetaert et al 2004, Elvisto 2010. The pattern of the highest leaf-nitrogen values in European clones followed by North American invasive and North American native genotypes (Guo et al 2014) was confirmed in our experiment.…”
Section: Nitrogen Phosphorus and Carbon In Leaves Rhizomes And Rootssupporting
confidence: 88%
“…Also the leaf-carbon values were close to maxima of 455-465 mg·g -1 reported from the field for European (Csatari et al 2015) and North American invasive plants (Schaefer et al 2014). The leaf phosphorus was comparable with the values, including maxima of 2.5-2.9 mg·g -1 , reported from the field in Europe (Baldantoni et al 2004, Elvisto 2010, Flury & Gessner 2014, Marchand et al 2014.…”
Section: Nitrogen Phosphorus and Carbon In Leaves Rhizomes And Rootssupporting
confidence: 87%
“…Previous studies also reported high efficiency of reed to remove nutrients (Álvarez-Rogel et al, 2006;Zhao et al, 2012), as well as heavy metals (Weis and Weis, 2004), from wetland soils. Foliar P concentrations in PC were much similar to those observed in PA, probably because a higher fraction of P was recycled from below ground tissues in PC compared with PA. Conversely, P concentrations in reed leaves in SM were several times lower than those usually recorded at nutrient-rich sites (see, for example: Ho, 1981;Elvisto, 2010;Ruiz and Velasco, 2010). Such low P concentrations in reed leaves in SM resulted in very high N : P ratios, suggesting that P limits reed growth in this community (Koerselman and Meuleman, 1996).…”
Section: Ecological Role Of Reed Stands and Effects Of Mowingmentioning
confidence: 84%
“…The third study site (Paljassaare) is in the eastern part of the Saartevahe Haak, a small bay at the tip of the Paljassaare peninsula in the Tallinn area on the Gulf of Finland. Overgrown with reed beds, it is a sandy beach zone with a marine sand layer, resulting from accumulating wave activity, which sits on till layers (Elvisto 2010). This site is not managed.…”
Section: Study Areamentioning
confidence: 99%